The Impact of the Judgments of the European Court of Human Rights on the Implementation of Constitutional Guarantees of Human Rights - V. V. Filatova (Теоретическая и прикладная юриспруденция)
The article is devoted to the implementation of the constitutional right of citizens of the Russian Federation to appeal to interstate bodies for the protection of human rights. The implementation of this right is considered on the example of the European Court of human rights and its rulings. The author gives an assessment of the changes in Russian legislation made on the basis of European Court rulings, as well as the difficulties faced by the state when reforming its legal system.